Platonic Stoicism, Stoic Platonism : the dialogue between Platonism and Stoicism in antiquity - Bonazzi, Mauro, 1973-; Helmig, Christoph (Ancient and medieval philosophy., 2007)
This book examines the important but largely neglected issue of the interrelation between Platonism and Stoicism in Ancient Philosophy. Several renowned specialists in the fields of Stoic and Platonic analyse the intricate mutual influences between Stoic and Platonic philosophers in the Hellenistic period, the Imperial Age, and after. Although it has been repeatedly claimed that the phenomenon addressed in this book could best be labelled eclecticism, it emerges from the various articles collected here that the situation is much more complicated. Far from being eclectics, most Stoics and Plato.